MODELING OF OPERATION OF COAXIAL-LINEAR MOTORS WITH AXIAL AND RADIAL DIRECTIONS OF MAGNETIZATION OF PERMANENT MAGNETS IN DYNAMIC MODE - G.M. Golenkov (National Technical University "Kharkiv Polytechnic Institute", 2014)
Theoretical and experimental investigations of the amplitude, phase and inertia-power frequency characteristics of two types of coaxial-linear electric motors of back-and-forth motion with permanent magnets, which magnetization vector is directed axially and radially relative to the axis of the runner are carried out. The comparative analysis of characteristics of these motors is presented.